Sinicization and validation of occupational burnout scale for nurses in operating room - Li, Yufang; Liu, Qiaoyan; Jiang, Yun; Cheng, Deyun; Yin, Wei (Frontiers in Public Health, 2025)
ObjectiveThis study aims to evaluate a burnout scale specifically developed for operating room nurses.MethodsThe Brislin translation model was utilized to translate and back-translate the scale. Following cultural adaptation and a preliminary investigation, the Chinese version of the Operating Room Nurse Burnout Scale was finalized. A convenience sampling method was employed to select 445 operating room nurses in Anhui Province as research participants to evaluate the scale's reliability and validity.ResultsThe Chinese version of the Operating Room Nurse Burnout Scale consists of 33 items, categorized into four dimensions: personal factors, occupational nature factors, interpersonal relationship factors, and organizational factors. The item-level content validity index (I-CVI) was 0.849, and the scale-level content validity index (S-CVI/Ave) indicated good content validity. Exploratory factor analysis yielded a Kaiser-Meyer-Olkin (KMO) value of 0.968, while Bartlett's test of sphericity demonstrated a chi-square value of 11,288 (p < 0.01). Four common factors were extracted, accounting for a cumulative variance contribution of 65.9%. The overall Cronbach's α coefficient was 0.968, the split-half Cronbach's α coefficient was 0.925, and the test-retest Cronbach's α coefficient was 0.974.ConclusionThe Chinese version of the Nurse Burnout Scale demonstrates robust reliability and validity, making it suitable for assessing burnout levels among operating room nurses.